2022
DOI: 10.3390/agronomy12020488
|View full text |Cite
|
Sign up to set email alerts
|

A Metallochaperone HIPP33 Is Required for Rice Zinc and Iron Homeostasis and Productivity

Abstract: Both zinc (Zn) and iron (Fe) are essential micro-nutrients for plant growth and development, yet their levels in plants are tightly regulated to prevent either deficiency or phytotoxicity. In agronomic reality, such an imbalance of metal bioavailability to crops occurs frequently. Thus, mining genetic resources to improve crop traits relevant to metal homeostasis is a great challenge to ensure crop yield and food quality. This study functionally identified an uncharacterized metallochaperone family HIPP protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…OsHIPP56 may co-work with the transporters to play that role. Our previous study showed that OsHIPP56 is expressed dominantly in node I, leaf blade, and husk [30], this pattern of OsHIPP56 expression could support the assumption that OsHIPP56 would function with some metal transporters to deliver Mn into seeds. Further investigation on the mechanisms for Mn accumulation in rice grains will be required.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…OsHIPP56 may co-work with the transporters to play that role. Our previous study showed that OsHIPP56 is expressed dominantly in node I, leaf blade, and husk [30], this pattern of OsHIPP56 expression could support the assumption that OsHIPP56 would function with some metal transporters to deliver Mn into seeds. Further investigation on the mechanisms for Mn accumulation in rice grains will be required.…”
Section: Discussionsupporting
confidence: 61%
“…OsATX1 plays an important role in Cd and Cu homeostasis [29]. OsHMP chelates Cd and Mn [26] and OsHIPP33 regulates homeostasis of Zn and Fe [30]. To functionally investigate OsHIPP56, the transcriptional expression of OsHIPP56 under Mn deficiency and excess was first characterized.…”
Section: Discussionmentioning
confidence: 99%
“…A Faraday collector configuration that employed the L5, L3, Ax, H2, H3 and H4 cups was used for the analyses, with all collectors fitted with 10 11 Ω resistors. Faraday collectors L3, Ax, H2 and H4 were employed to measure the ion beams of 64 Zn, 66 Zn, 67 Zn and 68 Zn, while L5 and H3 were used to monitor 62 Ni and 135 Ba 2+ to allow for spectral interference corrections of isobaric Ni + and Ba 2+ ions on the different Zn isotopes. Each sample measurement entailed three blocks of twenty 5 s integration cycles, with electronic baselines measured for 15 s prior to each block, during which the ion beam was deflected in the electrostatic analyser 52 .…”
Section: Sample Preparationmentioning
confidence: 99%
“…In the following, all δ 66 Zn values are reported relative to the JMC-Lyon Zn isotope standard. To this end, the initial results were corrected for a δ 66 Zn offset of + 0.28‰ for AA-ETH Zn relative to JMC-Lyon Zn 54 .…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation